PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Anisa Safitri; Ramdhan Witarsa; Nurmalina; Mohd. Fauziddin; Lusi Marleni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning activity of fifth-grade students at UPT SDN 020 Ridan Permai in the IPAS subject. The purpose of this research is to describe the improvement of student learning activity through the application of the Problem Based Learning (PBL) model. The research method used is classroom action research (CAR) conducted in two cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. The subjects of this research are 18 fifth-grade students at UPT SDN 020 Ridan Permai. The research instruments used include teacher activity observation sheets, student activity observation sheets, student activity sheets (LKPD), and documentation. These instruments are designed to assess activity indicators, including: actively participating in completing tasks, engaging in problem-solving, asking questions to teachers or peers, seeking relevant information, and discussing in groups. The results of the research show an increase in student learning activity from pre-action to cycle I by 4.8%, and an increase from cycle I to cycle II by 6.47%. Thus, overall, the increase in student learning activity reaches 11.27%. The application of the Problem Based Learning model has been proven to enhance the learning activity of elementary school students. Therefore, the application of this model needs to be consistently continued, and teachers require ongoing support to be able to implement the steps of PBL correctly according to the learning objectives.